Sex Hormone–Dependent Lipid Mediator Formation in Male and Female Mice During Peritonitis - Troisi, Fabiana; Pace, Simona; Jordan, Paul M.; Meyer, Katharina P. L.; Bilancia, Rossella; Ialenti, Armando; Borrelli, Francesca; Rossi, Antonietta; Sautebin, Lidia; Serhan, Charles N.; Werz, Oliver (Frontiers in Pharmacology, 2022)
Introduction: Sex differences in inflammation are obvious and contribute to divergences in the incidence and severity of inflammation-related diseases that frequently preponderate in women. Lipid mediators (LMs), mainly produced by lipoxygenase (LOX) and cyclooxygenase (COX) pathways from polyunsaturated fatty acids (PUFAs), regulate all stages of inflammation. Experimental and clinical studies revealed sex divergences for selected LM pathways without covering the entire LM spectrum, and only few studies have addressed the respective role of sex hormones. Here, we performed the comprehensive LM profile analysis with inflammatory peritoneal exudates and plasma from male and female mice in zymosan-induced peritonitis to identify the potential sex differences in LM biosynthesis during the inflammatory response. We also addressed the impact of sex hormones by employing gonadectomy. Methods: Adult male and female CD1 mice received intraperitoneal injection of zymosan to induce peritonitis, a well-established experimental model of acute, self-resolving inflammation. Mice were gonadectomized 5 weeks prior to peritonitis induction. Peritoneal exudates and plasma were taken at 4 (peak of inflammation) and 24 h (onset of resolution) post zymosan and subjected to UPLC–MS-MS–based LM signature profiling; exudates were analyzed for LM biosynthetic proteins by Western blot; and plasma was analyzed for cytokines by ELISA. Results: Pro-inflammatory COX and 5-LOX products predominated in the peritoneum of males at 4 and 24 h post-zymosan, respectively, with slightly higher 12/15-LOX products in males after 24 h. Amounts of COX-2, 5-LOX/FLAP, and 15-LOX-1 were similar in exudates of males and females. In plasma of males, only moderate elevation of these LMs was apparent. At 4 h post-zymosan, gonadectomy strongly elevated 12/15-LOX products in the exudates of males, while in females, free PUFA and LOX products were rather impaired. In plasma, gonadectomy impaired most LMs in both sexes at 4 h with rather up-regulatory effects at 24 h. Finally, elevated 15-LOX-1 protein was evident in exudates of males at 24 h which was impaired by orchiectomy without the striking impact of gonadectomy on other enzymes in both sexes. Conclusions: Our results reveal obvious sex differences and roles of sex hormones in LM biosynthetic networks in acute self-resolving inflammation in mice, with several preponderances in males that appear under the control of androgens.